PENERAPAN MEMBRAN MIKROFILTRASI PADA PEMURNIAN EKSTRAK KALDU KACANG HIJAU (Phaseolus radiatus L.) SEBAGAI FORTIFIKAN PRODUK MAKANAN - Aspiyanto Aspiyanto; Agustine Susilowati (Research Center for Chemistry - LIPI, 2010)
In preparation of mung bean (Phaseolus radiatus L.) broth extract asfortificant agent offood products via purification by means of microfiltration (MF) membrane, operation conditions have important role. Application of MF membrane modul is afurther process of purification from small scale (Stirred MF cell, 30.175 cm2 of membrane area) to bench-scale (Cross-flow MF modul, 360 cm2 of membrane area). The main goal of this work was to find out effect of flow rate of material and operation pressure on compositions of concentrate/retentate and permeate from mung bean broth extract as savoury (umami)-based fortificant agent offood products. Preparation of mung bean broth extract was conducted by introducing broth extract of crude mung bean to Cross-flow MF modul at pump motor frequency of l0 and 20 Hz, room temperature and operation pressure of 2, 4 and 6 bar, respectively. Investigation was performed on permeate flux value, and analysis was conducted on concentrate/retentate and permeate, covering on total solids, dissolved solid, total protein, dissolved protein, N-amino and salt. The result of experiment showed that pump motor frequency and operation pressure affect on concentrate/retentate and permeate compositions. Increase of pump motor frequency and operation pressure increase permeate composition, but they tend to be almost similar on concentrate/retentate of mung bean broth extract. Treatment combination at pump motor frequency of 20 Hz and operation pressure of 2 bar generated the best composition of concentrate/retentate as hydrolyzed vegetable protein (HVP) with concentrations of total solids of 3.98 %, soluble solid of 6.05 %, total protein of 5.65 %, dissolved protein of 5.3 mg/mL, N-amino of 0.95 mg/mL and salt of 2.04 %, while permeate gave flux value of 32.19 L/m2.hour with concentrations of total solids of 5.74 %, soluble solid of 5.04 %, total protein of 4.51 %, dissolved protein of 4.05 mg/mL, N-amino ofl.08 mg/mL and salt of 2.2 %, and had useful potency asfood savoury flavor.Keyword : Mung bean (Phaseolus radiatus L.) broth, microfiltration (MF), concenirate/reieniaie, permeate, hydrolysate.